Health-related physical fitness of normal, stunted and overweight children 6–14 years in Macedonia - Gontarev S.; Kalač R.; Aleksovska Veličkovska L.; Shukova-Stojmanovska D.; Misovski A.; Milenkovski J. (Hospital nutrition, 2018)
Objective: the objective of this study is to compare the growth and health-related physical fitness of normal, overweight/obese and stunted Macedonian children aged 6-14 years. Methods: this cross-sectional study included 9,241 children of Macedonian nationality, from 19 primary schools from the central and east part of the Republic, out of which eight are in a rural setting and eleven are in urban environment. In order to carry out the objectives of the research, four anthropometric measurements, two derived anthropometric measurements, two measurements for assessing body composition and seven fitness tests were applied. Normal-not stunted, not owt/ob; stunted-not owt/ob; and owt/ob-not stunted were compared with multivariate analysis of covariance controlling for socioeconomic status, residence status (urban or rural), sex, age and age squared. Results: statistically significant differences were found in all anthropometric measurements, and measurements for assessing body composition among the groups of subjects classified as normal, stunted and overweight/obese (p ˂ 0.000). Children who belong to the normal weight group achieve better results in all fitness tests (p < 0.001), except for the handgrip and bent arm hang tests. Overweight/obese children achieve better results in the handgrip fitness test compared to normal and stunted children. Stunted children achieve better results in the bent arm hang fitness test compared to normal and overweight/obese children. Intergroup differences were found in the sit and reach fitness test. Conclusion: when compared to normal weight children, both under- and over-nourished children performed poorer on some, but not all, health-related fitness tests.
Keywords: normal weight children, under- nourished children, over-nourished children, growth, health-related physical fitness